STRUCTURAL TRANSFORMATION IN WEST KALIMANTAN TOWARDS ASEAN ECONOMIC COMMUNITY 2015 - Memet Agustiar (Universitas Islam Indonesia, 2013)
AbstractThis paper explores the patterns of economic transformation in West Kalimantan during the last 40 years, calculates productivity, and examines the impact of agriculture sector decline on non-agricultural sector performance. It finds that economic transformation has taken place in West Kalimantan, and that the productivity of agricultural sector remains low. It also finds that the decline in agriculture sector increases the output of trade and manufacture sectors. The emergence of premature shift in the transformation process can be identified by the analysis. The results suggest initiating an outward-looking policy through an active participation within the sub-regional cooperation in ASEAN.Keywords: Economic transformation, productivity, ASEANJEL classification numbers: O13, O14AbstrakMakalah ini mengeksplorasi pola transformasi ekonomi di Kalimantan Barat selama 40 tahun terakhir, menghitung produktivitas sektoral, serta mengkaji dampak penurunan sektor pertanian terhadap kinerja sektor non-pertanian. Penelitian ini menemukan bahwa transformasi ekonomi telah terjadi di Kalimantan Barat, dan bahwa produktivitas sektor pertanian tetap rendah. Penelitian ini juga menemukan bahwa penurunan pangsa sektor pertanian mendorong kenaikan output di sektor perdagangan dan manufaktur. Munculnya pergeseran prematur dalam proses transformasi juga teridentifikasi oleh analisis yang dilakukan. Penemuan ini menyarankan perlunya kebijakan yang berorientasi keluar untuk melakukan partisipasi aktif dalam kerjasama sub-regional di ASEAN.Kata Kunci:Transformasi ekonomi, produktivitas, ASEANJEL classification numbers: O13, O14